Salmonella Typhi, Paratyphi A, Enteritidis and Typhimurium core proteomes reveal differentially expressed proteins linked to the cell surface and pathogenicity. - Sara Saleh; Sandra Van Puyvelde; An Staes; Evy Timmerman; Barbara Barbé; Jan Jacobs; Kris Gevaert; Stijn Deborggraeve (PLOS Neglected Tropical Diseases, 2019)
Background Salmonella enterica subsp. enterica contains more than 2,600 serovars of which four are of major medical relevance for humans. While the typhoidal serovars (Typhi and Paratyphi A) are human-restricted and cause enteric fever, non-typhoidal Salmonella serovars (Typhimurium and Enteritidis) have a broad host range and predominantly cause gastroenteritis. Methodology/principle findings We compared the core proteomes of Salmonella Typhi, Paratyphi A, Typhimurium and Enteritidis using contemporary proteomics. For each serovar, five clinical isolates (covering different geographical origins) and one reference strain were grown in vitro to the exponential phase. Levels of orthologous proteins quantified in all four serovars and within the typhoidal and non-typhoidal groups were compared and subjected to gene ontology term enrichment and inferred regulatory interactions. Differential expression of the core proteomes of the typhoidal serovars appears mainly related to cell surface components and, for the non-typhoidal serovars, to pathogenicity. Conclusions/significance Our comparative proteome analysis indicated differences in the expression of surface proteins between Salmonella Typhi and Paratyphi A, and in pathogenesis-related proteins between Salmonella Typhimurium and Enteritidis. Our findings may guide future development of novel diagnostics and vaccines, as well as understanding of disease progression.